Diversity Includes Disability: Experiences of Resilience in a University Residence (Journal of Student Affairs in Africa, 2021)
The provision of residence accommodation is a persistent challenge that is faced by universities across the globe. However, suitable accommodation for students with disabilities is an even greater challenge that is exacerbated by the absence of appropriately designed, maintained and managed residences. In particular, the adverse impact on wheelchair users and students whose disabilities require specific design adaptations is acute. This article will focus on the experiences of students with disabilities in university residences. The study on which this article is based employed a phenomenological theoretical approach with 'resilience' as the conceptual framework. The findings reveal that many stressors impacted students with disabilities in university residences and that these stressors potentially hampered their performance. However, these students developed personal attributes and ways of responding to the stressors they encountered, and many devised social networks utilisation to address their challenges and navigate institutional barriers. A particular focus was that embracing diversity is crucial for all operations at universities to counteract the discrimination and stigmatisation that are often experienced by students with disabilities.
Keywords: access; accommodation; belonging; diversity; resilience; students with disabilities